2009
DOI: 10.2754/avb200978030449
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose, Insulin and Inorganic Phosphorus in Healthy and Ketotic Dairy Cows after Intravenous Infusion of Glucose Solution

Abstract: The aim of the present study was to determine the degree of blood glucose utilization by peripheral tissue on the basis of changes in blood concentrations of glucose, insulin and inorganic phosphorus in healthy (n = 10) and ketotic cows (n = 10) after intravenous infusion of glucose solution. Blood samples were taken in both groups of examined cows at the following time intervals: just before (time 0) and 30, 60, 120, 180 and 240 min after intravenous infusion of a total of 500 ml of 50% of glucose solution. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
4
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
7
4
0
2
Order By: Relevance
“…of glucose was 143.7 pmol/L of insulin per 1 mmol/L of glucose in heathy cow vs. 107.14 pmol/L of insulin per 1 mmol/L of glucose in ketotic cow). Other authors have reported similar results (SAKAI et al, 1993;SAKAI et al1996;HOLTENIUS et al, 2003;DJOKOVIĆ et al, 2009). All of this shows that Pi response depends on insulin response to glucose, that is the presence of insulin resistance.…”
Section: R Cincović Et Al: Inorganic Phosphorus Decrease Is Assosupporting
confidence: 66%
“…of glucose was 143.7 pmol/L of insulin per 1 mmol/L of glucose in heathy cow vs. 107.14 pmol/L of insulin per 1 mmol/L of glucose in ketotic cow). Other authors have reported similar results (SAKAI et al, 1993;SAKAI et al1996;HOLTENIUS et al, 2003;DJOKOVIĆ et al, 2009). All of this shows that Pi response depends on insulin response to glucose, that is the presence of insulin resistance.…”
Section: R Cincović Et Al: Inorganic Phosphorus Decrease Is Assosupporting
confidence: 66%
“…Serum insulin levels showed a significant decrease in ketotic cows compared with control cows. Decreased serum insulin in ketotic cows is agreeable to that recorded by Sadeghi et al 2011and Djoković et al 2009.Moreover, the decreased serum insulin in ketotic cows is agreeable to that recorded by Ahmad et al, (2005); and Teli and Ali, (2007) in ketotic buffaloes. Decreased serum insulin levels could be attributed to the decreased ability of β-cells of the endocrine pancreas to synthesize and release insulin (Dokovic et al, 1998 andDjoković et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Decreased serum insulin in ketotic cows is agreeable to that recorded by Sadeghi et al 2011and Djoković et al 2009.Moreover, the decreased serum insulin in ketotic cows is agreeable to that recorded by Ahmad et al, (2005); and Teli and Ali, (2007) in ketotic buffaloes. Decreased serum insulin levels could be attributed to the decreased ability of β-cells of the endocrine pancreas to synthesize and release insulin (Dokovic et al, 1998 andDjoković et al, 2009). Low plasma insulin concentration reduces glucose uptake by nonmammary extrahepatic tissue and makes glucose available for uptake by the mammary gland which is not responsive to insulin (Bauman.,2000).…”
Section: Discussionsupporting
confidence: 89%
“…Hayirli (2006) and Koster and Opsomer (2013) have shown that low insulin concentrations exacerbate lipid mobilization and increase the plasma concentrations of NEFA, which in turn inhibit insulin-dependent glucose uptake in peripheral tissues by decreasing the expression of GLUT4, consequently reducing the sensitivity of these tissues to insulin. Another contributing factor is the relationship between the hypoinsulinemia and the ability of β-pancreatic cells to produce and release this hormone during hypoglycemia at disease onset (DJOKOVIĆ et al, 2009;2014). Hypoinsulinemia is directly associated with the increase in serum concentrations of NEFA, suggesting that the reduced anabolic effect of insulin on lipid metabolism results in the exacerbated mobilization of NEFA from body stores.…”
Section: Clinicalmentioning
confidence: 99%